THE UNCERTAINTY OF ORGANIZATIONAL ENVIRONMENT IN DEVELOPING COUNTRIES - Madinda, Alexander S. (International Journal of Emerging Trends in Science and Technology, 2014)
An organization’s environment normally can be well studied from two perfectives, which are the extent of change and the level of complexity. The extent of change considers the stability and instability of the environment and complexity of environment depends on the number of inconsistent pattern which are liable to vary and resulting in either complex or a simple environment. This paper therefore seeks to provide an overview of organizational environment, and discuss the uncertainty of organizational environment in developing countries. It started with the introduction of both terms organization and environment. It explains the developing countries perspective and the uncertainty of its environment, and identifies the factors that contribute to a grown climate of uncertainty in developing countries It goes on analyses the impact of uncertainty of environment towards organizational performance caused by political system, economic, socio cultural, legal, technology and demographic factors and tries to elaborate the best practice of SWOT analysis in managing organizational environment. After that it ended up by a conclusion. Keywords: Uncertainty, Organization, Environment, Developing Countries, Environmental forces, SWOT analysis.